Pengaruh Vanadil Sulfat Terhadap Ekspresi Protein GLUT-4 pada Mencit yang Menderita Diabetes Mellitus - Holidah, Diana; Khotib, Junaidi (Jurnal Farmasi Indonesia, 2012)
The Present study was designet to investigate the influence of vanadyl sulphate towards GLUT-4 protein activities in skeletal muscle tissue in streptozotocin induced diabetic mice. Twenty five mice divided into five groups i.e. placebo group, diabetic group, and three treatment groups based on vanadyl's doses (5,30 or 100 mg/kg BW, respectively). Diabetic mice model was induced by twice intraperitoneal administration of streptozotocin. The first dose of streptozotocin is 100 mg/kg that were inject in the first day and then dose 50 mg/kg, in the day 14th. Diabetes occured on 21st day after streptozotocin injection and it was shown by increasing blood glucose level from 151.4 ± 25.1 mg/dL to 237.1 ± 33.0 mg/dL. Administration of vanadyl sulphate at the dose of 5,30 or 100 mg/kg BW was significantly reduces blood glucose concentration (p<0,001). The muscular tissue were harvested on the day 28th and stained using routine histology staining, hematoxylin-eosin for morphological qualitative analysis and immunohistochemical examination to observe the activities of GLUT-4 protein in skeletal muscle. The result showed that vanadyl sulphate restore atrophic condition of muscular cells and inhibit cell necrosis in muscular tissue. On immunohistochemical examination, vanadyl sulphate might increased the GLUT-4 protein activities in skeletal muscle in streptozotocin-induced diabetic mice Keywords : vanadyl sulphate, streptozotocin, diabetes mellitus, GLUT-4 Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh vanadil sulfat terhadap aktivitas protein GLUT-4 pada otot skelet mencit yang menderita diabetes mellitus akibat induksi streptozotocin. Sebanyak 25 ekor mencit dibagi menjadi 5 kelompok, yaitu kelompok kontrol, diabtes dan perlakuan yang diberi vanadil sulfat dengan dosis 5,30 dan 100 mg/kgBB. Keadaan diabetes diinduksi dengan pemberian streptozotocin dosis 100 mg/kgBB pada hari pertama dan 50 mg/kgBB pada hari ke -14. Pada hari ke-21 terjadi peningkatan kadar glukosa dari 151,4 ± 25,1 mg/dL menjadi 237,1 ± 33,0 mg/dL. Pemberian vanadil sulfat selama 7 hari akan menurunkan kadar glukosa darah secara signifikan (p<0,001). Otot skelet diambil pada hari ke-28 dan dipreparasi dengan hematoksilin-eosin untuk diamati histologinya dan secara imunohistokimia untuk pengamatan aktivitas protein GLUT-4. Hasil pengamatan menunjukkan pemberian vanadil sulfat akan memperbaiki keadaan atropi dan menghambat nekrosis pada sel otot skelet. Pengamatan secara imonohistokimia menunjukkan bahwa vanadil sulfat dapat meningkatkan aktivitas GLUT-4. Kata Kunci: vanadil sulfat, streptozotocin, diabetes mellitus, GLUT-4